Determinant Analysis of The Role of Islamic Banking in Micro Small Medium Enterprises in The New Normal Period - Rahmayati, Rahmayati; Mujiatun, Siti; Khairi, Fadhli bin Wan Mahmud (Universitas Islam Negeri Raden Intan Lampung, 2023)
The purpose of this study was to identify and analyze the role of Islamic banking in MSMEs in the new normal period because Islamic banking is a financial intermediary institution that has a role in economic development and in this case the focus of research on MSMEs can drive economic activity. Problems in research due to this new normal period need to be studied whether MSMEs increase their income during the new normal period and whether Islamic banking has played a role. This research methodology was conducted using primary data obtained through a survey of 116 business actors engaged in the food business and other businesses located in the city of Medan. The results of this study indicate that MSMEs survive from their own capital in the form of assets and savings owned, even though the interest and desire of MSME actors is very dominant in wanting to transact to obtain assistance in the form of capital from Islamic banking, which is equal to 86%. 52.6% of MSMEs have capital problems in this new normal period. Thus it can be concluded that Islamic banking has not provided assistance to MSMEs in the new normal period and Islamic banking has the potential to increase its role as a financial intermediary institution in the future.